2015
DOI: 10.1139/bcb-2014-0150
|View full text |Cite
|
Sign up to set email alerts
|

Fasting upregulates adipose triglyceride lipase and hormone-sensitive lipase levels and phosphorylation in mouse kidney

Abstract: Circulating non-esterified fatty acids (NEFA) rise during fasting and are taken up by the kidneys, either directly from the plasma or during re-uptake of albumin from glomerular filtrate, and are stored as triacylglycerol (TAG). Subsequent utilization of stored fatty acids requires their hydrolytic release from cellular lipid droplets, but relatively little is known about renal lipolysis. We found that total [(3)H]triolein hydrolase activity of kidney lysates was significantly increased by 15% in the fasted st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Intracellular lipases needed to utilize triglyceride stored in lipid droplets also increased; hormone sensitive lipase (Hsl/Lipe) mRNA increased 7-fold and adipose triglyceride lipase (Atgl/Pnpla2) 2-fold. Others have reported that, after a fast, both HSL and ATGL activation by phosphorylation increases in the kidney(33). Taken together, this gene expression profile suggests that, despite increased mRNA levels of genes regulating FAO and decreased mRNA levels of genes mediating de novo lipogenesis, the kidney stores excess fatty acids in lipid droplets during fasting.…”
mentioning
confidence: 73%
“…Intracellular lipases needed to utilize triglyceride stored in lipid droplets also increased; hormone sensitive lipase (Hsl/Lipe) mRNA increased 7-fold and adipose triglyceride lipase (Atgl/Pnpla2) 2-fold. Others have reported that, after a fast, both HSL and ATGL activation by phosphorylation increases in the kidney(33). Taken together, this gene expression profile suggests that, despite increased mRNA levels of genes regulating FAO and decreased mRNA levels of genes mediating de novo lipogenesis, the kidney stores excess fatty acids in lipid droplets during fasting.…”
mentioning
confidence: 73%
“…In the same experiment, we examined the effects of fasting on mRNA and protein levels of two other LD proteins: adipocyte TG lipase (ATGL), the major lipase in LDs, and perilipin 2 (PLIN2), an LD protein that increases with TG accumulation in hepatocytes . ATGL mRNA levels increased with fasting, as expected . Despite the increase in ATGL mRNA, protein levels did not show a concomitant increase over the same time period.…”
Section: Resultsmentioning
confidence: 80%
“…(24) ATGL mRNA levels increased with fasting, as expected. (25) Despite the increase in ATGL mRNA, protein levels did not show a concomitant increase over the same time period. No correlation was found between the amount of PNPLA3 and ATGL on LDs.…”
Section: Delayed Clearance Of Pnpla3 During the Fed To Fasting Transimentioning
confidence: 89%
“…Standardized rodent diet (Research Diets #D12450H, New Brunswick, New Jersey, USA) and water were provided to the mice ad libitum for 9 days. Half of the mice were randomly chosen for a 16 h overnight fast from 5 pm to 9 am prior to cervical dislocation and tissue collection as we have previously described [1] . Protocols were approved by the Animal Care Committee at the University of Waterloo, with all procedures performed in accordance with the Canadian Council on Animal Care.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%